Impact of Chlorella vulgaris on the rheology of wheat flour dough and bread texture. (March 2018) - Graça, C.; Fradinho, P.; Sousa, I.; Raymundo, A.
Abstract: Modern foods lead to healthier, cheaper and more convenient products to increasingly demanding consumers. Microalgae are an enormous biological resource, representing one of the most promising sources for new products and applications and can be used to enhance the nutritional and technological value of food products. The enrichment of bread with microalgae biomass is a great challenge resulting from its impact on the development of the gluten structure. The addition of Chlorella vulgaris in a wheat flour dough was studied, to evaluate its influence on the dough rheology and bread texture. Microalgae contents from 1.0 to 5.0 g per 100 g of wheat flour were tested and it was observed that up to 3.0 g of microalgae biomass addition, a positive impact on dough rheology and viscoelastic characteristics, with strengthening of the gluten network, was observed. For higher microalgae content, a negative effect on dough rheology, bread texture and flavor was noticed and an acceleration on bread aging was relevant. No impact on the kinetics of yeast fermentation, neither on the time required for fermentation, was induced by the biomass addition. Highlights: Addition of Cv to wheat flour modified the rheological features of the bread dough. More than 3 g of Cv/ 100 g of WF has a negative impact on bread quality. Up to 3 g/100 g of Cv induces a gluten network reinforcement. Cv can be used to enrich bread with bioactive compounds. The incorporation of Cv induces changes in the aging kinetic of the bread.